Water shortage: Assessment and analysis on a regional scale - Yuri M. Macedo; Jhonathan L. de Souza; Adriano L. Troleis (Jàmbá)
This paper, adopting theoretical-methodological assumptions, aims to analyse the risk of municipal urban water shortage in the state of Rio Grande do Norte (RN), Brazil, through the results of the Water Shortage Risk Index (WSRI). The WSRI is the product of the analysis of 19 variables, in a systemic perspective that involves environmental, infrastructural, socioeconomic and state planning indicators. The survey was carried out in the 153 municipalities that make up the water supply system managed by the state concessionaire (representing 92% of the 167 municipalities in the State), in its seven water supply regions. The WSRI result identified 49.0% of the municipalities analysed in the ‘high’ and ‘very high’ risk classes; 40.5% as ‘medium’ risk and 10.0% as ‘low’ risk, with no occurrences of ‘very low’ risk. In absolute values, 1 municipality was classified as ‘very high’; 74 were classified as ‘high’; 62 as ‘average’; and 16 were considered to be at ‘low’ risk of water shortages.